2015
DOI: 10.2903/j.efsa.2015.4163
|View full text |Cite
|
Sign up to set email alerts
|

African swine fever

Abstract: Since entering the eastern EU at the start of 2014, African swine fever (ASF) has spread locally in the wild boar population, independently of outbreaks in domestic pigs. No correlation between the density of the wild boar population and the case notification in an area has been observed. The source of virus introduction appeared to be the low biosecurity level in backyard farms; yet, direct contact between pigs and wild boar has not been reported. Potential wild boar management strategies aimed at controlling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 93 publications
0
37
0
Order By: Relevance
“…Thoen et al (84) and Sánchez-Vizcaíno et al (50) also suggested that systems that wild boar can use as artificial feeding places (feeders, water holes, supplementary feeding of ungulates) should be avoided, as these systems can significantly increase wild boar abundance and spatial concentrations. However, it has been also suggested that this ban may be deemed effective only in regions where the habitat is unsuitable for wild boar and where feeding caused artificial population establishment (53). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thoen et al (84) and Sánchez-Vizcaíno et al (50) also suggested that systems that wild boar can use as artificial feeding places (feeders, water holes, supplementary feeding of ungulates) should be avoided, as these systems can significantly increase wild boar abundance and spatial concentrations. However, it has been also suggested that this ban may be deemed effective only in regions where the habitat is unsuitable for wild boar and where feeding caused artificial population establishment (53). …”
Section: Resultsmentioning
confidence: 99%
“…(16, 28, 48, 53). Finally, Mellor et al (68) observed experimental transmission of ASF through Stomoxys calcitrans flies.…”
Section: Resultsmentioning
confidence: 99%
“…There are multiple possible ways of the ASFV spreading, such as feeding animals with food waste [2,13], using contaminated transport facilities and care items, feeds, or staff errors [8,14]. In Denmark and the Netherlands, the transport facilities were recognized as one of the most important ways the classical swine fever (CSF) can spread with [15,16].…”
Section: Titers Of African Swine Fever Virus (Lg Haumentioning
confidence: 99%
“…The suitability, effectiveness and the practical aspects of implementation of the main measures was elaborated elsewhere (see EFSA AHAW Panel, 2015). The results presented here require bearing in mind the uncertainty around quantitative aspects related to the implementation needs and resource requirements of these ASF management options themselves, and knowledge gaps regarding ASF ethology as it affects behaviour of wild boar with clinical disease and the contact transmission between non-socialising individuals.…”
Section: Interpretation Of the Terms Of Reference 12mentioning
confidence: 99%
“…The model input consisted of the most recent experimental data on ASF, the wild boar habitat models and the ASF notifications from the affected countries, all as provided by EFSA (see EFSA AHAW Panel, 2015).…”
mentioning
confidence: 99%